2018
DOI: 10.1101/418012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic inflammation and risk of age-associated diseases in people living with HIV on long term suppressive antiretroviral therapy

Abstract: Objective(s):To assess the levels of systemic inflammatory markers of age-associated comorbidities in people living with HIV (PLHIV) on long term suppressive antiretroviral therapy (ART). Design:Prospective cross-sectional study in a well-defined Indian cohort of PLHIV.Methods: Blood samples were obtained from therapy naïve PLHIV (Pre-ART, n=43), PLHIV on ART for >5 years (ART, n=53), and HIV-negative healthy controls (HIVNC, n=41).Samples were analyzed for 92 markers of inflammation, sCD14, sCD163, telomere l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Other contributing factors that may promote biological aging and age-related comorbidities in HIV include antigen-driven proliferation, shortening of telomeres, accumulation of DNA damage, disruption of the stem cell niche, and stem cell exhaustion [33,108,132]. The end result of these processes is an environment that promotes low-grade inflammation, along with decreased lymphoid progenitors and an accumulation of senescent lymphocytes with less diverse T cell repertoires [133][134][135][136]. Unlike lymphoid progenitors, myeloid progenitors are not diminished, which may contribute to increased incidence of anemias and myeloid dysplasias [137,138].…”
Section: What Role Does Damage To Critical Hematopoietic Stem Cell Niches and Lymphoid Microenvironments By Hiv And Art Play In Age-relatmentioning
confidence: 99%
“…Other contributing factors that may promote biological aging and age-related comorbidities in HIV include antigen-driven proliferation, shortening of telomeres, accumulation of DNA damage, disruption of the stem cell niche, and stem cell exhaustion [33,108,132]. The end result of these processes is an environment that promotes low-grade inflammation, along with decreased lymphoid progenitors and an accumulation of senescent lymphocytes with less diverse T cell repertoires [133][134][135][136]. Unlike lymphoid progenitors, myeloid progenitors are not diminished, which may contribute to increased incidence of anemias and myeloid dysplasias [137,138].…”
Section: What Role Does Damage To Critical Hematopoietic Stem Cell Niches and Lymphoid Microenvironments By Hiv And Art Play In Age-relatmentioning
confidence: 99%
“…Authors would like to thank technical support received from Dr. Ponnuraj CP, Mrs. Gomathi, Mr. Kannan Muthuramalingam, and Mr. Sathya Murthi. This manuscript has been released as a Pre-Print at bioRxiv (73).…”
mentioning
confidence: 99%
“…Elevated systemic inflammation and machine learning predictions of inflammatory and neurological disease risks in HIV-1-infected persons from our previous studies also provide supportive evidence for the observed metabolic abnormalities associated with the central nervous system in HIV-1-infected individuals despite long-term suppressive ART. 3,4 To summarize, we identified alterations in levels of circulating metabolites that could increase the risk of FIG. 1.…”
mentioning
confidence: 99%